Cerebral venous thrombosis after spinal anesthesia: case report - Bisinotto,Flora Margarida Barra (2017)
Abstract Introduction Cerebral venous thrombosis (CVT) is a rare but serious complication after spinal anesthesia. It is often related to the presence of predisposing factors, such as pregnancy, puerperium, oral contraceptive use, and malignancies. Headache is the most common symptom. We describe a case of a patient who underwent spinal anesthesia and had postoperative headache complicated with CVT. Case report Male patient, 30 years old, ASA 1, who underwent uneventful arthroscopic knee surgery under spinal anesthesia. Forty-eight hours after the procedure, the patient showed frontal, orthostatic headache that improved when positioned supine. Diagnosis of sinusitis was made in the general emergency room, and he received symptomatic medication. In subsequent days, the headache worsened with holocranial location and with little improvement in the supine position. The patient presented with left hemiplegia followed by tonic-clonic seizures. He underwent magnetic resonance venography; diagnosed with CVT. Analysis of procoagulant factors identified the presence of lupus anticoagulant antibody. The patient received anticonvulsants and anticoagulants and was discharged on the eighth day without sequelae. Discussion Any patient presenting with postural headache after spinal anesthesia, which intensifies after a plateau, loses its orthostatic characteristic or become too long, should undergo imaging tests to rule out more serious complications, such as CVT. The loss of cerebrospinal fluid leads to dilation and venous stasis that, coupled with the traction caused by the upright position, can lead to CVT in some patients with prothrombotic conditions.